2009
DOI: 10.1007/s10157-008-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin water channels in mammals

Abstract: Water channels, aquaporins (AQPs), are a family of small integral plasma membrane proteins that primarily transport water across the plasma membrane. There are 13 members (AQP0-12) in humans. This number is final as the human genome project has been completed. They are divided into three subgroups based on the primary sequences: water selective AQPs (AQP0, 1, 2, 4, 5, 6, 8), aquaglyceroporins (AQP3, 7, 9, 10), and superaquaporins (AQP11, 12). Since no specific inhibitors are yet available, functional roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
227
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(238 citation statements)
references
References 77 publications
6
227
0
5
Order By: Relevance
“…Some AQPs work as strict water channels, yet others are permeable to a wide range of substances, including glycerol [Ishibashi et al 2009]; for this reason they are called aquaglyceroporins, such as AQP7, first identified in rat testis by Ishibashi et al [1997]. The function and the different distribution of AQPs in male and female reproductive systems were extensively revised by Huang et al [2006] and they encompass uterine imbibitions mechanisms, ovum transport, oviductal fluid balance, follicle maturation, blastocyst formation, embryo implantation, and spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Some AQPs work as strict water channels, yet others are permeable to a wide range of substances, including glycerol [Ishibashi et al 2009]; for this reason they are called aquaglyceroporins, such as AQP7, first identified in rat testis by Ishibashi et al [1997]. The function and the different distribution of AQPs in male and female reproductive systems were extensively revised by Huang et al [2006] and they encompass uterine imbibitions mechanisms, ovum transport, oviductal fluid balance, follicle maturation, blastocyst formation, embryo implantation, and spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…There are 13 members in the AQP family (AQP0-12), and the expression of one or more of these is ubiquitous in mammalian cells (see reviews : Jeyaseelan et al (2006), Ishibashi et al (2009)). These include the four aquaglyceroporins that also allow passage of glycerol (AQP3, 7, 9 and 10), the two superaquaporins (AQP11, 12) and the remaining seven are largely water-selective AQPs.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work has demonstrated localisation only in ES and provides evidence suggesting a role of AQP8 in sperm volume regulation (Yeung et al 2009). AQP0, the AQP expressed specifically in the eye (Ishibashi et al 2009), has also been found in the testis but only restricted to somatic cells including the Sertoli and Leydig cells (Hermo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on sequence homology, aquaporins can be divided into subgroups, comprising orthodox aquaporins, aquaglyceroporins and super-aquaporins ( Figure 3) (163,239,240). Ortodox aquaporins, comprising AQP0, AQP1, AQP2, AQP4, AQP5, AQP6 and AQP8, are highly selective for water, whereas aquaglyceroporins, comprising AQP3, AQP7, AQP9 and AQP10, show permeability to some neutral solutes as well, including glycerol and urea (239,240). Aquaglyceroporins also show sequence homology to the bacterial glycerol facilitator protein (GlpF) (241).…”
Section: Aquaporinsmentioning
confidence: 99%